Prevalence of Anaemia in Patients with Type-2 Diabetes Mellitus in the Absence of Renal Impairment: A Cross-sectional Study - Sandeep S Reddy (JCDR Research and Publications Private Limited, 2021)
Introduction: Despite an increasing incidence of diabetic nephropathy, undermining the renal production of Erythropoietin (EPO), there are significant number of studies being reported with anaemia among diabetic patients with renal insufficiency, implicating numerous theoretical pathogenesis. Its impact being ignored over the years among Indian contexts, women and men in rural Southern India are particularly vulnerable to anaemia. The associated risk factors and occurrence of anaemia in Type-2 Diabetes Mellitus (T2DM) can be seen even in the absence of renal insufficiency. Aim: To determine the prevalence of anaemia in T2DM patients with normal renal function and assessment of its association with sociodemographic characteristics, biochemical and haematological variables. Materials and Methods: A descriptive cross-sectional study was conducted for a period of six months from December 2018 to May 2019 on total of 150 patients with T2DM, attending the Outpatient Department, Rajarajeswari Medical College and Hospital, Bangalore, India. All the patients of either sex, aged between 18-60 years, with a duration of Diabetes Mellitus (DM) more than five years, with no renal involvement, were included in the study. All statistical analysis was done using Statistical Package for Social Sciences (SPSS) version 20.0. The Chi-square test, Z-test was used for data analysis. Results: Among the 150 subjects, 86 (57.3%) were classified to be anaemic, with a mean age of 53 years whereas, 64 (42.6%) were classified as non anaemics with a mean age of 50 years. The mean duration of diabetes was found to be 10.5 years among anaemics and 9.7 years among non anaemics. Compared to non anaemics subjects, drug therapy with both Oral Hypoglycaemic Agents (OHA) and insulin showed a statistically significant difference among diabetic subjects with anaemia. The high prevalence of normocytic anaemia (52.3%) suggests the importance of non renal causes of anaemia in diabetic patients. Conclusion: Patients with T2DM have an independent risk for anaemia irrespective of renal insufficiency, posing a significant adverse effect on the quality of life and the progression of the underlying disease with high cardiovascular morbidity and mortality. Hence, management of diabetic patients should include mandatory routine haematological tests, with consideration of advancing age and poor glycaemic control.